Drying of Tomato Using a Solar Dryer with LPG Backup - Chavda, T V; Kumar, Naveen (Journal of Agricultural Engineering, 2009)
Tomato constitutes an integral part of the human diet worldwide. Although, tomato is commonly consumed fresh, over 80% of tomato consumption comes from processed products such as tomato juice, paste, puree, ketchup and sauce. The dried tomatoes are used for decorating some food dishes in stared hotels, in preparing some specific items like pasta, dal and vegetables. An indirect, forced convection solar cabinet dryer with LPG back up was tested for tomato drying by Sardar Patel Renewable Energy Research Institute (SPRERI). A 60 mÂ² packed bed solar collector was used to capture solar radiation for heating the drying medium (air) during the daytime, while a LPG burner was used to supply heat when enough solar energy was not available to get the desired drying temperature. The heat generated from the LPG burner was supplied to the incoming air through a heat exchanger. The temperature inside the drying chamber could be maintained around 80degree C for 9 h. This dryer is by no means limited to drying of the tomato. Currently, seven dryers of similar design have been used by farmer and industrial groups in Gujarat and Maharashtra states for drying ayurvedic medicines, mushroom, handmade paper, wooden planks, aonla and other products.